Assimilation of Javanese Art and Tradition in Sunan Kalijaga's Da'wah on the Formation of Javanese Culture - Belkis Nurbaiti; Ahmad Rubayu (Journal of Islamic Civilization and Culture Review, 2025)
This study analyzes the assimilation of Javanese art and tradition in the da'wah of Sunan Kalijaga and its contribution to the formation of Javanese Islamic culture. The research addresses the problem of understanding how Islamic teachings were accepted in a predominantly Hindu–Buddhist Javanese society without cultural resistance. Using a qualitative descriptive method supported by textual and historical analysis, this study examines how Sunan Kalijaga employed wayang kulit, gamelan, symbolic aesthetics, and macapat poetry as media of cultural adaptation. The findings show that Sunan Kalijaga did not reject existing traditions, but reinterpreted and Islamized them by embedding moral teachings, monotheistic concepts, and ethical values within familiar cultural forms. This approach strengthened social acceptance, minimized cultural disruption, and enabled Islam to integrate harmoniously with Javanese identity. The assimilation of arts and traditions not only facilitated da'wah but also shaped a distinctive Javanese Islamic culture characterized by refinement, symbolism, and spiritual depth. The study concludes that Sunan Kalijaga’s method represents an effective cultural strategy for religious propagation, demonstrating that Islam can coexist with local traditions without losing its essential principles. Further research is recommended to explore comparative models of cultural da'wah in other regions